2021
DOI: 10.22438/jeb/42/5/mrn-1648
|View full text |Cite
|
Sign up to set email alerts
|

Soil carbon, microbial biomass carbon, soil health and productivity of toria (Brassica campestris L.) crop as affected by the application of organic manures

Abstract: Aim: To investigate the effect of different organic manures on the performance of toria crop and to understand their impact on the soil properties and availability of nutrients in acidic sandy loam soil. Methodology: Three-year fixed plot study was conducted with 7 treatments viz., T1: control, T2: recommended dose of fertilizers (RDF), T3: cow dung manure @ 5 t ha-1, T4: pig dung manure @ 5 t ha-1, T5: goat dung manure @ 5 t ha-1, T6: farm yard manure (FYM) @ 5 t ha-1, and T7: vermicompost @ 5 t ha-1 replica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
1
0
0
Order By: Relevance
“…were not conducive to soil organic carbon xation and reduced the humi cation coe cient. Gogoi et al (2018) reported that application of pig manure signi cantly enhanced SOC content and our results agree with this (Gogoi et al 2021). This might be because pig manure has low C/N and high soluble matter, which make it easy to be decomposed by microorganisms and can release soluble matter into the soil more quickly after application, which improves SOC accumulation (Thangarajan et al 2013).…”
Section: Effects Of Different Treatments On Soc Content and Humus Com...supporting
confidence: 93%
“…were not conducive to soil organic carbon xation and reduced the humi cation coe cient. Gogoi et al (2018) reported that application of pig manure signi cantly enhanced SOC content and our results agree with this (Gogoi et al 2021). This might be because pig manure has low C/N and high soluble matter, which make it easy to be decomposed by microorganisms and can release soluble matter into the soil more quickly after application, which improves SOC accumulation (Thangarajan et al 2013).…”
Section: Effects Of Different Treatments On Soc Content and Humus Com...supporting
confidence: 93%